Legionella Infection in Pregnancy: The Forgotten Pathogen in Septic Shock. Issue 5 (November 2015) - Xu, Jack; Odibo, Imelda N.; Eastham, Donna G.; Dajani, Nafisa K.
Abstract : BACKGROUND: Of eight cases of Legionella infection in pregnancy reported over 35 years, there was one case of maternal septic shock with poor outcome, one recovery with good outcome, and six with poor outcome. CASE: A 30-year-old woman, gravida 2 para 1, at 28 weeks of gestation presented with a high fever, cough, nausea, and vomiting. She deteriorated despite treatment for presumed urosepsis, was transferred to the intensive care unit, and remained intubated for 10 days receiving cardiovascular support, antivirals, antifungals, and multiple wide-spectrum antibiotics. Legionella infection antigen testing was performed on hospital day 1 and returned as positive. Azithromycin, started before the testing results became available, was continued for 14 days. The patient recovered, and the pregnancy progressed uneventfully to term. CONCLUSION: Legionella infection should be considered with maternal deterioration despite broad-spectrum antibiotic coverage. A favorable outcome is possible with early diagnosis and treatment. Abstract : Legionnaires disease should be considered when an infection does not respond as expected.